Logical Image Migration Based on Overlays - Meehean, Joe; Quinn, Greg (University of Wisconsin-Madison Department of Computer Sciences, 2006)
Virtual machine technology is becoming an increasingly popular vehicle for enabling process and service migration. Many migration frameworks rely on a distributed file system to avoid worrying about the burden of migrating a large virtual disk. While this assumption is valid in some contexts, there are other environments where it is not feasible. In these cases, disk migration becomes the primary bottleneck for achieving efficient migration. We discuss the design, implementation, and evaluation of LIMBO, a system for efficient migration of VM local file systems. We've found that overlay-based migration using a copy-on-write block device can significantly improve migration costs while imposing a small amount of overhead on file system operations.